If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3a + -1(12 + -1a) = 16 3a + (12 * -1 + -1a * -1) = 16 3a + (-12 + 1a) = 16 Reorder the terms: -12 + 3a + 1a = 16 Combine like terms: 3a + 1a = 4a -12 + 4a = 16 Solving -12 + 4a = 16 Solving for variable 'a'. Move all terms containing a to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 4a = 16 + 12 Combine like terms: -12 + 12 = 0 0 + 4a = 16 + 12 4a = 16 + 12 Combine like terms: 16 + 12 = 28 4a = 28 Divide each side by '4'. a = 7 Simplifying a = 7
| 5x+3-2x=-2 | | 3-3(4-8x)=0 | | 0.72-1.4= | | h=-16tsquared+48t+4 | | 1x=4y-7 | | .3x-.5=.2x+8 | | 12x-4+18x+4+15x+10+5=360 | | 6x-6-3x-3=-6 | | -4x+4x=-8-32 | | w+5-(2w+5)=5 | | y=1/0 | | I/3+6=10 | | 8=4u+53+5u | | y=1/1-1 | | 3g+57g+4= | | 0.6x-.3=.5x+5 | | 3-6(8x+2)=9 | | 4x+(-8)=12 | | 5x+4y=79 | | 3-(r+3)=-14-3r | | -2x+6x=45 | | 5x+4x=79 | | -2(3t-5)+4t=5t-6 | | 8-4x+7=5x+30-2 | | 5(x+1)+8=3x+2(5+x) | | 18x-48y= | | 3(x+5)=4 | | 6.2x-3+x-1.2= | | 3(6-z)=-z(2) | | 1+4x=5x+28 | | 9.5(9k-3)=-24.5 | | 50v^2-98= |